Organizational Commitment Is Viewed From The Perception Of Organizational Support For Students Who Study While Working - Rahman, Saoki; Muharsih, Lania; Hakim, Arif Rahman (Psikoborneo: Jurnal Ilmiah Psikologi, 2023)
Students who decide to study while working have to take on a tougher role than students who don't work. The negative impact of studying while working is feeling that the work they do has no meaning, there are students who choose to resign from the company for several reasons, such as wanting to focus on completing their final assignment, choosing to look for a new job because of the long shift system, there are also students who often refuse to work overtime when asked by their superiors, it is in this situation that students' commitment is tested. Meanwhile, companies need employees who are proactive and have a high commitment to work. This research looked at the influence of organizational support on organizational commitment in 319 students who studied while working at UBPK. The sampling method uses quota sampling. In this study, 2 scales were used: the Allen and Meyer organizational commitment scale with 24 items and the Eisenberger perceived organizational support scale with 8 items. The SPSS 25 statistical program was used to analyze this research data. The results of the hypothesis test show a significance of 0.000 P <0.05. With an R coefficient value of 0.752, it is clear that the variable perception of organizational support has a positive impact on organizational commitment. This means that the more positive the perception of organizational support, the higher the level of commitment to the organization.Mahasiswa yang memutuskan untuk kuliah sambil bekerja harus menempuh peran yang lebih berat daripada mahasiswa yang tidak bekerja. Dampak negatif dari kuliah sambil bekerja adalah merasa bahwa pekerjaannya yang dilakukan tidak memiliki makna, adanya mahasiswa yang memilih untuk mengundurkan diri dari perusahaan dengan beberapa alasan, seperti ingin memfokuskan diri untuk menyelesaikan tugas akhir, memilih mencari pekerjaan baru karena sistem shift yang berkepanjangan, ada juga mahasiswa yang sering menolak lembur ketika diminta oleh atasan, di situasi tersebutlah komitmen mahasiswa diuji. Sedangkan perusahaan membutuhkan karyawan yang proaktif dan memiliki komitmen yang tinggi dalam bekerja. Penelitian ini melihat pengaruh dukungan organisasi terhadap komitmen organisasi pada 319 mahasiswa yang kuliah sambil bekerja di UBPK. Metode pengambilan sampelnya menggunakan kuota sampling. Dalam penelitian ini, digunakan 2 skala: skala komitmen organisasi Allen dan Meyer dengan 24 item dan skala persepsi dukungan organisasi Eisenberger dengan 8 item. Program statistik SPSS 25 digunakan untuk menganalisis data penelitian ini. Hasil uji hipotesis menunjukkan signifikansi 0.000 P <0,05. Dengan nilai koefisien R sebesar 0,752, jelas bahwa variabel persepsi dukungan organisasi berdampak positif pada komitmen organisasi. Artinya semakin positif persepsi dukungan organisasi maka semakin tinggi tingkat komitmen pada organisasi